2018
DOI: 10.1016/j.ophtha.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary and Macular Vessel Density in Patients with Primary Open-Angle Glaucoma and Unilateral Visual Field Loss

Abstract: OCT-A measures detect changes in retinal microvasculature before VF damage is detectable in patients with POAG, and these changes may reflect damage to tissues relevant to the pathophysiology of glaucoma. Longitudinal studies are needed to determine whether OCT-A measures can improve the detection or prediction of the onset and progression of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
98
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 51 publications
13
98
1
2
Order By: Relevance
“…Previous studies have reported that the AUROC values for macular VD that ranged from 0.562 to 0.800 for distinguishing between early glaucoma and normal eyes [26,27,30,34]. However, little is known about the diagnostic ability of macular VD in detecting PPG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the AUROC values for macular VD that ranged from 0.562 to 0.800 for distinguishing between early glaucoma and normal eyes [26,27,30,34]. However, little is known about the diagnostic ability of macular VD in detecting PPG.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative OCT-A metrics have been shown to associate with retinal vein occlusion,4 glaucoma,5 6 diabetes7–9 and kidney dysfunction, showing a role in identifying microvascular abnormalities. Importantly, these changes in retinal microvasculature can be detected before clinical stage, for example, in patients with diabetes without clinical retinopathy signs,7 8 and in glaucomatous eyes before visual field damage,10 demonstrating that OCT-A is capable to identify preclinical pathological processes involving retinal microvasculature.…”
Section: Introductionmentioning
confidence: 99%
“…11,14,24,25 RPC density showed a significant diagnostic ability to differentiate normal from glaucoma eyes, comparable to that of OCT. 13,22,26,27 It has also been reported that peripapillary microvascular changes may precede vision field loss. 11,12,19,[27][28][29][30] The preperimetric stage of glaucoma, defined as nerve fiber damage without detectable defects in standard automated perimetry (SAP), remains a challenging diagnosis which could be facilitated by OCTA. However, it is still under discussion whether the assessment of RPC density could help in preperimetric glaucoma (PPG) detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still under discussion whether the assessment of RPC density could help in preperimetric glaucoma (PPG) detection. 13,15,20,[26][27][28][29][30][31] The aim of the present study was to investigate the vascular status of the optic disc and peripapillary area in association with the structural changes in patients with unilateral PPG.…”
Section: Introductionmentioning
confidence: 99%